Debris flow and landslide forecast based on gis and doppler weather radar in liangshan prefecture - Jiang, Y.H.; Wei, F.Q; Zhang, J.H.; Deng, B.; Xu, A.S. (Italian journal of engineering geology and environment, 2011)
Debris flow and landslide forecast is an important means of disaster reduction. This paper took Liang- shan Yi Autonomous Prefecture, Sichuan Province as the study area. Analyzing distribution rules of debris flow and landslide under different underlying surface’s conditions, it used the extension theory to erect to debris flow forecasting model and the information content analysis method to erect the landslide forecasting model. These models obtained 3 hours’ forecasting precipitation by processing some Doppler weather radar products. The debris flow and landslide forecasting system in Liangshan Prefecture based on GIS was put into use in Liangshan Meteorological Observatory and could provide the future 3 hours’ debris flow and landslide forecast. Experimental results showed that the forecasting results have fine reliabilities.